Importance evaluation of praesacral nerves block in the treatment of chronic prostatitis/chronic pelvic pain syndrome - Mašková, Věra; Urban, Michael; Heráček, Jiří (Abstracts of the 2nd Czech and International Congress of Andrology, 2007)
Evaluation of successfulness of new therapeutic strategy (biofeedback + praesacral nerves block) compared with still used treatment. Material and methods: Prospective study of 20 patients who were examined according to our given protocol: laboratory and urodynamic examinations (P/Q study), subjective evaluation of live quality and level symptoms severity-National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), duration period of symptoms. Urinary infection and bacterial prostatitis were exclusion criteria. Results: Medium term of follow up was (17 months, range 8–26). Duration period of symptoms was 1 year to 10 years. 3 patients (15%) were found to have obstructive voiding disorders according to P/Q study, that was further treated, equally 3 patients (15%) were found to have overactive bladder symptoms. 14 patients (70%) with normosenzitive stable detrusor praesacral nerves block + biofeedback was accomplished. 11 patients (78.57%) gave satisfactory effect, 3 patients (21.43%) gave no effect. Start of effect was between 1 day and 1 week, duration of effect was from 3 months to 6 months. There were no complications. Conclusions: Our given therapeutic strategy is miniinvasive method with medium-term up to long-term effect. Results showed, that patients with initial milder intensity (severity) of symptoms evaluate treatment effect favourably that is by low index than patients with longstanding, severe symptoms. Nowadays is obvious that urodynamic examination and NIH-CPSI will play the determinantal role as for separation of patients as for evaluation quality, severity and prognosis of disease. To identify treatments that might help prevent acute problems from becoming chronic, it will be the subject of continuation that study.